Structured optimization of QRS duration reduction post-Cardiac Resynchronization Therapy is feasible and shorter QRS duration is associated with better clinical outcome. (19th May 2022) - Borgquist, R; Marinko, S; Platonov, PG; Wang, L; Chaudhry, U; Mortsell, D
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Cardiac resynchronization therapy (CRT) is an established treatment for heart failure in selected patients(1). A recently developed device-based algorithm for optimization of AV- and VV-timing (SyncAV) has shown promising acute hemodynamic improvement by tailoring the device settings for maximum reduction in QRS-duration(2). We aimed to evaluate if optimization by maximizing QRS reduction is feasible in an all-comer CRT population and if reduced QRS-duration is associated with a better clinical outcome. Methods: Medical records of 254 consecutive patients with left bundle branch block receiving CRT implants during the period 2015-2020 were retrospectively evaluated. Implants from 2015-2017 were designated as control group. Typical programming in the control group included a short AV-time to ensure biventricular capture and synchronous pacing of the right and left ventricle, or in selected patients a slight preexitation (20-40 ms) of the left ventricle. Starting from 2018 and onwards, an active 12-lead electrogram (ECG) based optimization of QRS duration had been implemented and these patients were designated as the intervention group. QRS duration and morphology were evaluated in a structured way at various device settings, including use of specific device algorithms when applicable and manual modifications of AV- and VV-delays and LV only pacing when applicable, aiming to maximize reduction of QRS duration. Digital ECGs before and after CRT implantation were collected and QRS duration reduction was automatically analyzed. The primary endpoint was a composite of heart failure hospitalization or death from any cause. Results: Patients were followed for up to 6 years (median 2.9 [1.8-4.1]), during which 82 patients (32%) reached the primary endpoint; 53 deaths (21%) and 58 (23%) heart failure hospitalizations. Median QRS duration pre-implant was 162ms [150-174] and post-implant 146ms [132-160]. Mean reduction in QRS duration was progressively larger for each year during the intervention period, changing from -9.5ms in the control group to -24 in the year 2020 (p=0.005). In Kaplan Meier analysis across all groups, QRS reduction >14ms (median value) was associated with lower risk of death or heart failure hospitalization (p=0.049). In a multivariate model the hazard ratio was 0.60 [0.38-0.96] (p=0.03). Conclusion: Implementing a general strategy of CRT device-optimization by aiming for shorter QRS duration is feasible in a structured clinical setting, and results in larger reductions in QRS duration post-implant. In patients with larger QRS reduction, compared to those with smaller QRS reduction, there is an association with a better clinical outcome, including lower risk of mortality and heart failure hospitalization. If confirmed in prospective trials, this strategy may become useful for improving clinical outcome for CRT recipients, regardless of device-brand and underlying etiology.